Konsep dan Implementasi Kurikulum Merdeka Dalam Pendidikan di Indonesia - Mufidah, Seyma; Muttofi'ah, Rianita; Dzira Vania Putri Purnomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Merdeka Curriculum represents the newest educational strategy crafted by Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi aimed at enhancing learning standards following the COVID-19 pandemic while also refining the 2013 Curriculum. This curriculum emphasizes adaptable learning, a student-focused approach, and the promotion of character development through the Pancasila Student Profile. The objective of this research is to evaluate how effectively the Merdeka Curriculum is being applied in enhancing the educational quality in Indonesia. A literature study employing a qualitative descriptive methodology was utilized as the research method. Data was gathered from 25 scholarly articles, and after a selection process, 10 pertinent articles were examined. The findings show that the Merdeka Curriculum's implementation positively influences educational quality, including fostering creativity, promoting learning autonomy, developing 21st-century competencies, and enhancing teacher professionalism. Nevertheless, several obstacles remain in its execution, such as inadequate facilities and infrastructure, inconsistent teacher training, and unequal educational quality across different schools. Consequently, ongoing training, regular oversight, and equitable policy support are essential to fully realize the Merdeka Curriculum's implementation across Indonesia.